A study on saving behavior among Bumiputera on Amanah Saham Wawasan 2020: Utilization of personal selling to increase the market share / Khairul Anuar Mahpol (Faculty of Business Management, 2007)
Nowadays, most Malaysians are more interested in investing their money with the intention to increase their savings. This is because they are more concerned towards the future of themselves in terms of family, children as wen as a step for protection if the rainy days come unexpectedly. Therefore, as an organization that expert in the field of investment, Amanah Saham Nasional Berhad offers this service in fulfilling the demand of Malaysians. Amanah Saham Nasional Berhad is offering several types of unit trust that promise profits for every single cent that customer invest in Amanah Saham Nasional Berhad. This study was conduct to know the relationship between saving behavior and demographic profile of the respondents. The other factors are to know the relationship between factors influencing investment in Amanah Saham Wawasan 2020 with the approach by the sales people of Amanah Saham Nasional Berhad. There are 50 respondents answering the questionnaire that are given to them. This study using non probability sampling which is convenient sampling. This non probability sampling is used since it relies on the personal judQment of the researcher rather than chance to select sample elements. Therefore, this study will discuss on how to increase savings amon Bumiputera and to determine the understanding of Bumiputera about Amanah Saham Nasional Berhad. This study will only focus on the relationship between Amanah Saham Wawasan 2020 (which is Amanah Saham Nasional Berhad products -unit trust) and Bumiputera.